The Influences of Sales Agents Personal Selling on The Nissan Serena Car Brand Image - Indra Yustika; Baharuddin, Aris; Sulmiah; Yusi Irensi Seppa (Fakultas Ilmu Sosial dan Hukum, 2024)
This study aims to determine how much influence the Personal Selling Sales Agent has on the Brand Image of Nissan Serena PT. Wahana Megahputra Makassar, Lamojong Branch. This study uses a quantitative method of descriptive analysis research with data collection techniques through observation, questionnaires, and documentation. The sample used in this study was the entire population, namely 73 respondents. The data of this study were obtained from the results of data processing using the SPSS 25 application which consisted of validity and reliability tests, descriptive data analysis techniques and inferential analysis. The results of this study indicate that the Personal Selling Sales Agent variable on the Nissan Serena Car Brand Image PT. Wahana Megahputra Makassar Lamojong Branch has a significant influence. This is evidenced by the results of a simple linear regression test and a correlation coefficient test of 0.919, which means that the relationship between Personal Selling and Brand Image is very high. The coefficient of determination is obtained at 0.813 which means that the influence of Personal Selling Sales Agents on the Brand Image of Nissan Serena PT. Wahana Megahputra Makassar, Lamojong Branch, got a score of 81.3% which was included in the very high category interval.